Demographic Behaviour and Earnings Inequality across OECD Countries - Leo Azzollini; Richard Breen; Brian Nolan (Luxembourg Income Study (LIS), 2023)
Many studies have focused on how demographic dynamics, such as changes in marriage patterns and the increasing share of households headed by a single adult, may contribute to rising earnings inequality. Here we instead ask how demographic differences between countries may underpin differences in household earnings inequality between them, concentrating on economic homogamy and the proportion of households headed by a single woman and by a single man. We use data on 28 OECD countries from the 2016 wave of the Luxembourg Income Study, and develop a new inequality decomposition approach based on half the squared coefficient of variation (HSCV). We find that variation between countries in the specified demographic factors can account for just above 40% of the variation between countries in inequality in household labour earnings, with the proportion of households headed by a single woman playing the largest role. The associations between labour earnings inequality and these demographic components are consistent across countries, with little variation in how each is related to overall inequality. Although by far the largest driver of crossnational inequality relates to the earnings of partnered men, counterfactual analysis suggests that relatively small changes in these demographic variables can indeed affect inequality.
Keywords: 330; Earnings Inequality; Economic homogamy; Household structure; Inequality decompositions; OECD countries